Effect of vitamin C supplementation on immune status and oxidative stress in pregnant Murrah buffaloes during thermal stress - GANAIE, A H; HOODA, O K; SINGH, S V; ASHUTOSH, ASHUTOSH; UPADHYAY, R C (The Indian Journal of Animal Sciences, 2013)
The experiment was conducted to study the effect of vitamin C on oxidative stress and immune status in buffaloes during summer. Primiparous Murrah buffaloes (12) in late gestation were used for this study. The buffaloes were divided into 2 groups of 6 animals each. Group 1 was served as control and group 2 was supplemented with ascorbic acid @ 10g/animal/day from day –45 to day 0 (day of parturition). Blood samples were collected on days –45, –30, –7 and 0. Lymphocyte proliferation index (LPI) and neutrophil phagocytic activity (PA) were analyzed in the whole blood. Plasma was analyzed for, antioxidant enzymes (SOD, CAT and GPx). The PA decreased and the decline was significant on day –7 and day 0 in both groups compared to day –45. The PA was significantly (lower in group 2). LPI was significantly lower on day 0 compared to day –45 in both groups but the variations between groups were not significant. SOD, CAT and GPx activity increased significantly from day –45 to day 0 in both groups. However, the increase in their activity was significantly lower in group 2 compared to group 1. Plasma TAS decreased 12.3 and 6.8% in group 1 and group 2, respectively, from day –45 to day 0 and overall levels were significantly higher in group 2 than group 1. TBARS increased with advancement of pregnancy and the levels were significantly higher on day –7 and 0 in both groups. The levels of TBARS were significantly higher in group 1 compared to group 2. The results indicated that the deviations in immune status and oxidative stress caused due to thermal stress restored towards normalcy by supplementation of vitamin C.